Visual attention in orienteers at different levels of experience - Eccles, D. W.; Walsh, S. E.; Ingledew, D. K. (Journal of Sports Sciences, 2006)
This study explored how differences in orienteering experience are related to differences in how visual attention is allocated to the map, the environment and to travel. Twenty more experienced and 20 less experienced individuals orienteered while wearing a head-mounted video camera with microphone. The participants verbalized what they were attending to (map, environment or travel) at any given time. Each recorded film was coded at each point in time in terms of what the participant was attending to and whether the participant was moving or stationary. More experienced orienteers attended to the map markedly more while moving and spent less time stationary than less experienced orienteers. The participants' performance was significantly related to the ability to attend to the map while moving. The strategic control of attention is proposed to explain this ability. It is proposed that attentional training might enhance performance in sports characterized by multiple and dynamically varying elements.